Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.